A GHz rotary nanoflake driven by diamond needles: A molecular dynamics study. (June 2020) - Shi, Jiao; Wang, Aiqin; Song, Bo; Cai, Kun
Abstract: In this study, we build a nanostirrer, in which the circular graphene nanoflake can be driven to rotate on graphite substrate by four wedged diamond needles (DNs). Molecular dynamics simulations reveal that the rotationally distributed DNs provide strong repulsion to the nanoflake via their tip atoms. Once the circumferential component of the repulsive force is non-zero, it actuates the flake to rotate at gigahertz. The stable rotational frequency (SRF) of the flake can be obtained when the friction moment from substrate balances the driving moment from DNs. Results also demonstrated that, at temperature lower than 100 K, stronger compression from DNs will introduce larger SRF to the flake due to stronger driving force from the DNs. Under the same conditions, a smaller flake has higher SRF. When changing the layout angles of DNs in a range with width of 90°, both the SRF and rotational direction of the nanoflake change monotonously. These characteristics suggest a clue for design of a nano-stirrer with controllable rotation for potential applications, e.g., separation and purification or generating nanoflow field through the gigahertz rotary flake. Graphical abstract: Unlabelled Image Highlights: A nano-stirrer model from carbon materials is proposed. Below 100 K, the blade in nano-stirrer has higher stable rotational frequency (SRF) when compressed tighter by diamond needles (DNs). A smaller blade has higher value of SRF when they are actuated by the same DNs. By changing the layout angles of DNs in a range, SRF varies from negative to positive monotonously.